Clinical characteristics and risk factors for severe COVID‐19 in hospitalized kidney transplant recipients: A multicentric cohort study. Issue 11 (23rd September 2020) - Favà, Alexandre; Cucchiari, David; Montero, Nuria; Toapanta, Nestor; Centellas, Francisco J.; Vila‐Santandreu, Anna; Coloma, Ana; Meneghini, Maria; Manonelles, Anna; Sellarés, Joana; Torres, Irina; Gelpi, Rosana; et al.
Abstract : Kidney transplant recipients might be at higher risk for severe coronavirus disease 2019 (COVID‐19). However, risk factors for relevant outcomes remain uncertain in this population. This is a multicentric kidney transplant cohort including 104 hospitalized patients between March 4 and April 17, 2020. Risk factors for death and acute respiratory distress syndrome (ARDS) were investigated, and clinical and laboratory data were analyzed. The mean age was 60 years. Forty‐seven patients (54.8%) developed ARDS. Obesity was associated to ARDS development (OR 2.63; P  = .04). Significant age differences were not found among patients developing and not developing ARDS ( 61.3 vs 57.8 years, P  = .16). Seventy‐six (73%) patients were discharged, and 28 (27%) died. Death was more common among the elderly (55 and 70.8 years, P  < .001) and those with preexisting pulmonary disease (OR 2.89, P  = .009). At admission, higher baseline lactate dehydrogenase (257 vs 358 IU/mL, P  = .001) or ARDS conferred higher risk of death (HR 2.09, P  = .044). In our cohort, ARDS was equally present among young and old kidney recipients. However, the elderly might be at higher risk of death, along with those showing higher baseline LDH at admission. Abstract : This multicenter study of kidney transplant recipients with COVID‐19 analyzes the clinical course and immunosuppression adjustments during infection and investigates risk factors for severe forms.